2020
DOI: 10.1111/jfpp.14802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of hydrocolloids on viscosity and cloud stability of kinnow juice and beverages

Abstract: Cloud stabilization in fruit juices and beverages add increased esthetic appeal of the products. Pulp particles in bottled fruit juices and beverages like nectars, squashes, crush etc. tend to coalesce and settle at the bottom or float at the top leaving a clear or hazy serum, which results in an unattractive appearance of the product. Cloud in citrus juices is made up of finely divided particles of pulp, natural pigments, and flavoring oil. Particles of pigments and flavoring oil are small enough to be subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…Similar results were reported by Aggarwal et al. (2020) for kinnow juice. Smaller particles tend to be suspended in the juice and transfer less light through it; hence, greater absorbance is measured with a spectrophotometer (Aghajanzadeh et al., 2017).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Similar results were reported by Aggarwal et al. (2020) for kinnow juice. Smaller particles tend to be suspended in the juice and transfer less light through it; hence, greater absorbance is measured with a spectrophotometer (Aghajanzadeh et al., 2017).…”
Section: Resultssupporting
confidence: 92%
“…Similar behaviors were also observed by Aggarwal et al. (2020). The viscosity of bi‐gel‐incorporated juice is found to be always greater than that of hydrogel‐incorporated ones, revealing that the synergism of KC and KGM is better, compared to that of KC and whey.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This is considered a characteristic of non‐Newtonian pseudoplastic fluids. Kinnow juice containing different hydrocolloids including gum acacia, pectin, guar gum and sodium alginate also showed mostly Newtonian to pseudoplastic behavior, 34 which was consistent with our study. In this work, raw juice (S1) had a higher viscosity than the other juice samples, followed by juice after centrifugation at 2000 × g (S2) and 4000 × g (S3).…”
Section: Resultssupporting
confidence: 91%
“…In addition, other studies examining the effect of hydrocolloid addition on the viscosity and sensory characteristics of raspberry-juice milk showed that the addition of CMC improved the viscosity and stability of products, compared to products with added hydrocolloid pectin and kappa-carrageenan. Research on the addition of hydrocolloid type variations in the corn starch–rice flour system showed that the addition of hydrocolloids of any type increased the viscosity significantly [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%